2021
DOI: 10.1186/s12882-020-02227-4
|View full text |Cite
|
Sign up to set email alerts
|

Target value of mean arterial pressure in patients undergoing continuous renal replacement therapy due to acute kidney injury

Abstract: Background Although patients undergoing continuous renal replacement therapy (CRRT) due to acute kidney injury (AKI) frequently have instability in mean arterial pressure (MAP), no consensus exists on the target value of MAP related to high mortality after CRRT. Methods A total of 2,292 patients who underwent CRRT due to AKI in three referral hospitals were retrospectively reviewed. The MAPs were divided into tertiles, and the 3rd tertile group ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Relatively higher MAP cut-off levels were suggested for CRRT patients. A retrospective study of 2,292 AKI patients who underwent CRRT reported that MAP < 82.7 mmHg at the initiation of CRRT was associated with 1.21 (1.01-1.45)-fold higher odds of mortality 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Relatively higher MAP cut-off levels were suggested for CRRT patients. A retrospective study of 2,292 AKI patients who underwent CRRT reported that MAP < 82.7 mmHg at the initiation of CRRT was associated with 1.21 (1.01-1.45)-fold higher odds of mortality 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing MAP from 65 mmHg to a normal level was associated with improved microcirculation in hypertensive septic shock patients [ 20 ]. Mean arterial pressure < 82 mmHg was also observed to have increased mortality in patients starting continuous renal replacement therapy [ 21 ]. The optimal MAP can be further determined in the future for emergent hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The compare_categories workflow (QIIME 1.9.1) was used to perform Permutational analysis of variance (PERMANOVA) on the distance matrices to test for dissimilarities between groups. Differences in the taxa relative distribution between categories were tested using analysis of composition of microbes (ANCOM) [ 50 ]. The observation_metadata_correlation workflow (QIIME 1.9.1) was used to find Pearson correlations between specific operational taxonomic units (OTUs) and tetanus vaccine specific immunoglobulin (Ig) G level with subsequent FDR correction (Q value) in Study A, B and C. Correlations were conducted using the QIIME script observation_metadata_correlation.py.…”
Section: Methodsmentioning
confidence: 99%